Outcomes Associated With Fibrin Sealant Use in Lateral Neck Dissections. Issue 4 (December 2020) - Stanisce, Luke; Lai, Michael; Ahmad, Nadir; Spalla, Thomas C.; Reid, Lisa M.; Gaughan, John P.; Koshkareva, Yekaterina
Objective: To determine whether the use of fibrin sealant tissue adhesives during lateral neck dissections is associated with a change in postoperative outcomes. Study Design: Retrospective cohort. Setting: Institutionally affiliated tertiary care center. Methods: Various demographic, disease, and surgical data were collected for patients who underwent lateral neck dissections. Univariate regression analysis was performed with the following outcomes: total drain output and duration of drain placement, as well as incidence of postoperative infection, hematoma, seroma, chyle leak, and salivary leak. Results: A total of 133 patients underwent lateral neck dissections. Fibrin sealant was used in 35% of cases (n = 46). Its use was not associated with differences in total drain output ( P = .77) or the number of days that the drains were in place ( P = .83). On secondary analysis, the use of fibrin sealant was not associated with a difference in postoperative incidence of hematoma ( P = .65), seroma ( P = .68), chyle leak ( P = .42), or salivary leak ( P = .73). These results were consistent when stratified by the presence of intraoperative complications. Its use accompanied an average cost of $674 per case. Conclusions: Fibrin sealant use during lateral neck dissections was not associated with a reduction in drain output or days that the drains remained in situ. Although the current study was limited by sample size, fibrin sealant use was not associated with a decreased risk of postoperative adverse events. The evidence in this report suggests that the routine use of these products adds cost without clear benefit.